Pengaruh Pendidikan Kewirausahaan dan Lingkungan Keluarga Terhadap Intensi Berwirausaha Melalui Efikasi Diri pada Siswa SMK Negeri 14 Jakarta - Agnes Sarumpaet; Agus Wibowo; Maulana Amirul Adha (Teewan Journal Solutions, 2025)
This research aims to determine the influence of entrepreneurship education, and family environment on entrepreneurial intentions through the mediation of self-efficacy of students at SMK Negeri 14 Jakarta. This research was conducted for 4 months starting from August to November. The method used in this research is a survey method. The respondent selection technique used Proportional Random Sampling so that the sample obtained was 140 from class XII students at SMK Negeri 14 Jakarta. Data collection was carried out through distributing questionnaires using a Likert scale. The data analysis technique used is SEM (Structural Equation Model) with the help of the SmartPLS 4 program. Based on the results and discussion, it can be concluded that this research shows that there is a positive and significant direct influence between entrepreneurial education on entrepreneurial intentions, there is a positive and significant direct influence between entrepreneurial education on self-efficacy, there is a positive and significant direct influence between the family environment on entrepreneurial intentions, there is no positive and significant direct influence between the family environment on self-efficacy, there is a positive and significant direct influence between the family environment and self-efficacy. positive and significant between self-efficacy on entrepreneurial intentions, there is a positive and significant indirect influence between entrepreneurial education on entrepreneurial intentions which is mediated by self-efficacy, there is no positive and significant indirect influence between the family environment on entrepreneurial intentions which is mediated by self-efficacy.